Effects of strength training on osteogenic differentiation and bone strength in aging female Wistar rats - Singulani, Monique Patricio; Stringhetta-Garcia, Camila Tami; Santos, Leandro Figueiredo; Morais, Samuel Rodrigues Lourenço; Louzada, Mário Jefferson Quirino [UNESP]; Oliveira, Sandra Helena Penha [UNESP]; Chaves Neto, Antonio Hernandes [UNESP]; Dornelles, Rita Cássia Menegati [UNESP] (Springer Nature, 2017)
The effects of strength training (ST) on the mechanical bone strength and osteogenic differentiation of bone marrow mesenchymal stromal cells (BMSCs) from adult, aged and exercised aged rats were determined. The exercised aged animals displayed higher values of areal bone mineral density, compression test, alkaline phosphatase activity (ALP) and biological mineralization, while oil red O staining for adipocytes was lower. ST increased gene expression of runt-related transcription factor 2 (Runx2), osterix (Osx) as well as bone matrix protein expression, and reduced expression of peroxisome proliferator-activated receptor gamma (Pparγ 3). The production of pro-inflammatory cytokine tumor necrosis factor alpha (TNF-α) was lower in BMSCs of the aged exercised group. The ST practice was able to improve the bone mechanical properties in aged female rats, increasing the potential for osteogenic differentiation of BMSCs, reducing the adipogenic differentiation and pro-inflammatory cytokine level. In summary, the data achieved in this study showed that strength training triggers physiological responses that result in changes in the bone microenvironment and bring benefits to biomechanical parameters of bone tissue, which could reduce the risk of fractures during senescent.